Re-examining feminity - the voices of leadership in managerial meeting discourse - Kesumawati A. Bakar, (Penerbit UKM, 2005)
This paper contends that some of the communicative strategies employed by Malay women academic administrators are the antithesis of expected gendered speech patterns that could be triggered by the demands of leadership as well as an expression of individuality. Their observed communicative patterns contradict gender expectations and breach normative female communicative behavior. This paper chronicles the voices of 3 women academic administrators – as they project their individuality and construct their gender identities that defy gender stereotypes – and from new understandings reexamines the theory of language and gender within the context of managerial meeting discourse. Apart from understanding individual communicative styles of Malay women academic administrators, what this paper aims to demonstrate is the variation in communicative styles that exists within one gender of the same ethnic group, to re-examine the standard dichotic gender paradigm used in language and gender studies and consequently to reaffirm the concept of multiple femininities.